Two-dimensional silicene composite nanosheets enable exogenous/endogenous-responsive and synergistic hyperthermia-augmented catalytic tumor theranostics - Duan, Huican; Guo, Haiyan; Zhang, Ruifang; Wang, Fangfang; Liu, Zhuang; Ge, Min; Yu, Luodan; Lin, Han; Chen, Yu (Biomaterials, 2020)
Silicene as an emerging two-dimensional material (2DM) spurs the broad research interests due to its prominent electronic and physical properties, however, still lacking in exploitation for the biological and medical practices. Herein, we constructed a 2D silicene-based theranostic nanoplatform, MnOx@silicene-BSA (MS-BSA), with tumor microenvironment (TME)-responsive and synergistic hyperthermia-augmented catalytic activity when irradiated by near infrared-II (NIR-II) laser because of the high photothermal-conversion efficiency of 2D silicene matrix. Such MS-BSA nanosheets possess the capability to react with glutathione (GSH) to generate Mn2+ and glutathione disulfide (GSSG) under acidity/reducing TME condition. With the presence/assistance of HCO3−, the released Mn2+ exhibited sensitive catalytic activity towards endogenous H2O2via Fenton-like reaction, enabling the generation of highly toxic hydroxyl radicals (•OH), which finally led to the enhanced nanocatalytic therapeutic efficacy followed by exogenous NIR-II laser exposure, originating from hyperthermia-augmented catalytic activity. Especially, these MS-BSA nanosheets accumulated into the tumor region to enable superb contrast enhancement of TME-responsive T1-weighted magnetic resonance imaging (MRI) and photoacoustic imaging (PAI), and high-efficient in vivo synergistic tumor eradication. Therefore, such an intelligent photothermal-enhanced catalytic theranostic nanoplatform could realize the exogenous/endogenous-responsive and cooperative hyperthermia-augmented tumor treatment and accurate tumor positioning/monitoring. A 2D silicene-based theranostic nanoplatform, MnOx@silicene-BSA (MS-BSA) has been designed and constructed with tumor exogenous/endogenous-responsive and synergistic hyperthermia-augmented catalytic activity. Highly dispersed manganese oxide (MnOx) nanoparticles were in-situ grown onto the surface of silicene nanosheets by triggering the redox reaction on 2D surface. After further modification on the surface with bovine serum albumin (BSA), the as-prepared MS-BSA composite nanosheets acted as a multifunctional theranostic nanoplatform that integrated the intriguing multiple performances including magnetic resonance imaging (MRI), photoacoustic imaging (PAI), and synergistic photonic hyperthermia and Mn-catalyzed nanocatalytic therapy based on Fenton reaction. [Display omitted]